Mobile Malware Classification Based On Phylogenetics - Madihah Mohd Saudi; Sazali Sukardi; Amirul Syauqi Mohamad Syafiq; Azuan Ahmad; Muhammad ‘Afif Husainiamer (Blue Eyes Intelligence Engineering and Sciences Publication, 2024)
Indexed by SCOPUS